Legal actions and unfair competition: Examining the case law - Juppet Ewing, Fernanda; Pérez Lasserre, Diego (Derecho Público Iberoamericano, 2020)
The purpose of this work is to elucidate the requirements that both the Court of Appeals and the Antitrust Court have indicated that must be fulfilled for the exercise of a legal action to be considered asa right’s abuse. The article identifies the doctrinal differences between the decisions enacted by both courts.